STUDI TINGKAT KEBUGARAN JASMANI SISWA SEKOLAH MENENGAH PERTAMA MUHAMMADIYAH 6 - Akbar, Fadli; Bakhtiar, Syahrial; Hardiansyah, Sefri; Febrian, Mario; Syahrial Bakhtiar; Sefri Hardiansyah; Mario Febrian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of physical fitness among students at Muhammadiyah 6 Junior High School in Padang. This is a descriptive study using a quantitative approach. The sample consisted of 31 male students selected using purposive sampling. Data collection was conducted using the Indonesian Student Physical Fitness Test (TKSI), which included the standing broad jump, sit-up test, Ttest, hand-eye coordination test, and beep test. Data analysis techniques utilized frequency distributions and percentages. The results showed that the students’ physical fitness levels fell into the moderate category, with an average score of 14.645. A total of 67.74% of students fell into the moderate category, 22.58% into the poor category, and 9.67% into the good category. Thus, the students’ overall level of physical fitness falls into the moderate category and is not yet optimal, so it needs to be improved through regular and sustained physical activity